Strategies of Teaching Vocabulary for 8th-Grade SMPN 25 Surabaya - Amanda, Azzahrawaani Asy-Syifaa’ Qalb Aisyah; Muhtarom; Gunairawati, Junaenik Latiefah (ICONELT, 2024)
Vocabulary is a basic thing that must be mastered when learning English. However, the teaching methods employed by teachers may often be boring for grade 8 students, leading to a lack of motivation to learn new vocabulary, how teachers introduce vocabulary is crucial to how many words students can recognize and understand. This study aims to investigate the vocabulary teaching strategies used by teachers and the strategies preferred by grade 8 students at SMPN 25 Surabaya, focusing on the impact of these strategies on students’ academic achievement. This qualitative research utilized questionnaires and interviews with both teachers and students to gather data. The data analysis of data from interviews and questionnaires involved a systematic approach. Including transcription and coding of the responses. The teacher employs various vocabulary teaching strategies, including games like the word chain game, which fosters an interactive learning environment and helps students understand and remember new vocabulary by relating it to other materials, such as tenses. Students express a preference for digital media, such as videos and games, noting that these methods enhance their understanding and engagement. They also highlighted the effectiveness of conversation practice in the form of role-playing for vocabulary acquisition, although some strategies, such as using movies and songs, were not utilized in their lessons.